Analisis Dampak Polusi Udara Akibat Kebakaran Hutan Dan Lahan Serta Upaya Pengurangannya Dalam Mempertahankan Ketahanan Energi - maulia, siti tiara (Universitas Gadjah Mada, 2023)
ABSTRACTThis article raises problems that are being experienced and felt directly by Indonesia at this time. Indonesian people have to survive amidst air pollution, which is mostly caused by forest and land fires. These forest and land fires then have an impact that is also detrimental to various other sectors. Forests have various natural resources that contain a lot of energy and other potential that can be used in various forms of life. This impact can then gradually weaken the state of energy security in Indonesia. In order to overcome the negative impacts of air pollution caused by the spread of land and forests, it is important to understand that this is not just the task of